Respons Pertumbuhan Vegetatif Beberapa Varietas Tebu (Saccharum officinarum L.) terhadap Pemberian Mikoriza Arbuskular - Agustinus Prihartono; Albertus Sudirman; Abdul Azis (Jurnal Agro Industri Perkebunan, 2016)
Sugarcane (Saccharum officinarum L.) is a major source of commercial sugar production. Sugar is a commodity that is essential for the people of Indonesia both as a basic requirement as well as industrial raw material of food or beverage. Sugar demand is increasing with population growth and increasingly diverse array of foods. This study aims to determine the effect of mycorrhizal appropriate biological fertilizer for vegetative growth of sugarcane varieties of GMP and its interactions. Research carried out in the experimental garden of the State Polytechnic of Lampung, from July to December 2014. The method used was a randomized block design (RBD) factorial pattern, consisting of two treatment factors. The first factor was the rate of biofertilizers mycorrhizae which consisting of four levels, namely: M0 = 0 g of biofertilizers mycorrhizae per polybag, M1 = 10 g of biofertilizers mycorrhizae per polybag, M2 = 20 g of biofertilizers mycorrhizae per polybag and M3 = 30 g of biofertilizers mycorrhizae per polybag. The second factor was the varieties of sugarcane consisting of three varieties, namely: V1 = GMP1, V2 = GMP2 and V3 = GMP3. The results were analyzed using analysis of variance then continued with test least significant difference (LSD) 5%. The results showed that the effect on the variety of plant height and number of tillers. Mycorrhizal treatments and their interaction does not give effect to all parameters.Keywords: mycorrhizae, Saccharum officinarum L., vegetative growthPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/32